Encyclopaedia of religion and ethics; v. 12 - Hastings, James; Selbie, John A.; Gray, Louis H. (Edinburgh, Scotland T and T Clark, 1915)
Contents : v. 12 : Suffering - Zwingli
Keywords: Religion -- encyclopaedias; Ethics -- encyclopaedias